(untitled) (Religious dialogue and cooperation, 2021)
The article addresses the phenomenon of trafficking with human beings, focusing specifically on the religious component of preventing this phenomenon. To study this phenomenon, it is necessary to study the causes of human trafficking in Kosovo from a religious point of view. Concerning this negative phenomenon which has also spread at a global level, Kosovo, as a new and developing state, has built legal infrastructure for the prevention, protection, treatment and reintegration of victims of human trafficking in Kosovo. The functioning of the above is being carefully considered. The research question is: How does religion impact the prevention of trafficking in human beings in Kosovo? Relevant literature that has dealt with this phenomenon from a religious perspective is used for this theme in the study. To study this phenomenon, knowledge and factual data are used on the history of the development of this phenomenon. Factual data coming from relevant institutions in Kosovo (dealing with this phenomenon in Kosovo) is used to evaluate and measure the effectiveness of preventing human trafficking in Kosovo. The methodology used for the study of the phenomenon will focus on the methods: deductive, historical, statistical, comparative, etc. Secondary data are used for assessments and measurements of the development of the phenomenon, which will be obtained from relevant institutions of Kosovo. From the data and assessments on the development of the phenomenon results will be drawn on the effectiveness of the functioning and impact of the religious system on prevention of trafficking in human beings in Kosovo. We find that religion contributes to the raising of consciousness and morality of the people, and it exposes the ugly activity of trafficking in human beings in Kosovo. Overall, we find that families at risk of trafficking in human beings in Kosovo have a low standard of living, and Social schemes currently operating in Kosovo are not sufficient to cover all social categories that need social assistance.